Aesthetic Archives: Pre-Service Teachers Symbolizing Experiences through Digital Storytelling - Aitken, Avril; Radford, Linda (Journal of the Canadian Association for Curriculum Studies, 2012)
With the novelty of digital storytelling, there is increased enthusiasm in taking up forms of filmmaking in teacher education as a way to promote self-directed reflective practices. However, the visual quality of digital stories holds blind spots, in other words, what we defend against seeing in these approaches, as well as their implications for meaning making. With this in mind, the authors undertook a multi-year process that involved having pre-service teachers work with the aesthetic medium of digital storytelling to engage with critical incidents in their teaching. In this context, digital storytelling works as an aesthetic archive that symbolizes the conflicts of learning to teach. This article focuses on a close reading of two cases which provide insight into the ways in which future teachers use digital storytelling to both wrestle with and question the significance of the identity-making venture of becoming teachers. Additionally, the authors consider the personal and social implications of such an undertaking for teacher-educators.